1) Dada a função f(x) = -3x + 3, calcule:
a) f(-1) =
b) f(0) =
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
1) Dada a função f(x) = -3x + 3, calcule:
dica:
a) f(-1) = (-1) está dizendo que (x = - 1)
f(x) =- 3x + 3
f(-1) = - 3(-1) + 3
f(-1) = + 3 + 3
f(1) = 6
b) f(0) = dizendo que (x = 0)
f(x) = - 3x + 3
f(0) = - 3(0) + 3
f(0) = 0 +3
f(0) = 3
Perguntas interessantes
Filosofia,
8 meses atrás
Matemática,
8 meses atrás
Inglês,
9 meses atrás
Português,
9 meses atrás
Matemática,
1 ano atrás